Thermal protection and pH-gated release of folic acid in microparticles and nanoparticles for food fortification. Issue 2 (24th January 2020) - Osojnik Črnivec, Ilja Gasan; Istenič, Katja; Skrt, Mihalea; Poklar Ulrih, Nataša
Abstract : Dispersed folic acid was successfully encapsulated in alginate–pectin hydrogels, proliposomes, and combinations thereof, providing an efficient pH-responsive delivery system. Abstract : Encapsulation provides efficient approaches to increase stability and delivery of poorly soluble bioactive components, predominantly for fortification of beverages and similar liquid-based foods. In this study, folic acid was encapsulated within conventional and emulsion-templated alginate–pectin hydrogels, proliposomes, and a combination thereof. The stability of these systems was examined under various environmental conditions (pH 1.2–9.0, 25–85 °C, dark/light). The techniques demonstrated efficient and relatively straightforward production of well-defined microparticles and nanoparticles (350 nm to 250 μm). Dispersed folic acid provided a delivery system with unique pH-responsive features, which offered prolonged stability during food storage, and indicated increased release at the site of absorption upon ingestion. This formulation had no limitation due to particle size, while at the same time it allowed high encapsulation efficiencies (80%–100%), as compared to the low encapsulation efficiency achieved by solubilisation (6%). At the low pH that is expected in the stomach, leaching of the dispersed folic acid was prevented, while at the pH that is expected in the intestine, there was complete release via solubilisation and carrier swelling. Overall, the optimum for food processing and storage was pH 3.0, where ≥70% of 50% to 200% of the recommended daily allowance of folic acid remained in the alginate–pectin beads after 6 months at room temperature in the dark. The thermal properties were enhanced by emulsion-templated alginate–pectin beads and proliposomes. In this way, 30% to 75% retention of folic acid was achieved at temperatures ≤90 °C, where the proliposomes reinforced within a polysaccharide network achieved the highest level of protection.